Ð–Ð¸Ð·Ð½ÐµÑÐ¿Ð¾ÑÐ¾Ð±Ð½Ð¾ÑÑ‚ÑŒ ÑÐ¿Ð¾Ñ€Ð¾Ð²Ð¾Ð¹ ÐºÑƒÐ»ÑŒÑ‚ÑƒÑ€Ñ‹ Streptomyces fradiae Ð’ÐÐ˜Ð˜Ð“-25Ðâ€™ Ð¿Ð¾ÑÐ»Ðµ Ð²Ð¾Ð·Ð´ÐµÐ¹ÑÑ‚Ð²Ð¸Ñ Ð½ÐµÐºÐ¾Ñ‚Ð¾Ñ€Ñ‹Ñ… Ñ„Ð°ÐºÑ‚Ð¾Ñ€Ð¾Ð² Ð¿Ñ€Ð¾Ñ†ÐµÑÑÐ° Ð»Ð¸Ð¾Ñ„Ð¸Ð»Ð¸Ð·Ð°Ñ†Ð¸Ð¸ - Tsutsayeva, A. A.; Ananyiina, A. E.; Pavlenko, N. V. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2004)
There was studied the effect of residual humidity indices and rehydration ways on the viability and antibiotic activity after freeze-drying of Streptomyces fradiae VNIIG-25â€™ spore culture. It was demonstrated, that in order to obtain the highly active samples of frozen-dried microbial culture the optimal indices of a residual humidity corresponded to 1.0-2.0% and the rehydration was carried-out by one-step addition of distilled water with following exposure for 1 hr under 20Â°C.